Government Strategies On Co-Operatives During The Covid-19 Pandemic In Supporting Economic Resilience - Dalimunthe, Anantha Andhikatama; Suwito; Tumanggor, Muliahadi; Asmoro, Novky (Journal of Management, 2023)
Pandemic disease outbreaks are one of the non-physical non-military threats with a public safety dimension, when the covid-19 pandemic that occurred in early 2020 affected the world economy as well as in Indonesia, one of the affected sectors was the Cooperative, especially regarding finance. This study uses Lykke's strategy theory which includes 3 (three) aspects of Ends (Purpose) explaining "what" is to be achieved, Ways (Ways) strategic concepts / actions and Means (Means) explaining what specific resources will be used in applying concepts to achieve goals that must be balanced there will be no risk with descriptive qualitative methods this paper discusses how the strategies implemented by the government in helping Cooperatives during the Covid-19 Pandemic in supporting Indonesia's economic resilience, the results obtained between the three policies issued by the government have been implemented by the institutions concerned have been balanced and the risks have been minimal and the strategy has been running in helping Cooperatives during the covid-19 pandemic